MILITARY SPECIAL OPERATIONS IN THE INSURGENCY PERIOD IN BORNO STATE AND LAKE CHAD REGION: NATIONAL AND INTERNATIONAL EFFORTS - Kullima, PhD, Shettima Bukar; Attah, PhD, Smart Chikwere; Garba, Abdullahi (Journal of Public Policy and Administration, 2020)
Purpose: Nigeria military together with other multi-national military formations have been battling insurgency in Borno state and other parts of the Lake Chad region since 2009. This necessitated this paper titled "Military Special Operations in the Insurgency Period in Borno State and Lake Chad Region: National and International Efforts". The purpose of this study is to show how protracted nature of the insurgency has prompted various military special operations of national and international collaborations in the affected territories. Methodology: By so doing, the efficacies or otherwise of these operations were examined. This paper was based on secondary and primary analysis of data drawn from texts and oral interviews. Findings: The paper revealed that the military operations have been admixed with ups and downs. It was however shown from the paper that challenges leading to some operational challenges in the fight against insurgency are largely caused by both traditionally known operational difficulties and atypical professional ingress of the security personnel. So far, the prolonged nature of the conflict is partly as a result of this qualms in the military operational lineups as well as metamorphic nature of the insurgents' tactics. Unique contribution to theory, practice and policy: On this note, the paper concluded that relevant stakeholders should device other non-military approaches as alternative to address the lingering insurgency in the Lake Chad region. As such, the paper has contributed in supporting the postulations that robust efforts in counter-insurgency is essential, which include proper military coordination and other non-lethal policies.